Intra-articular delivery of micronized dehydrated human amnion/chorion membrane reduces degenerative changes after onset of post-traumatic osteoarthritis - Lin, Angela S. P.; Reece, David S.; Thote, Tanushree; Sridaran, Sanjay; Stevens, Hazel Y.; Willett, Nick J.; Guldberg, Robert E. (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Micronized dehydrated human amnion/chorion membrane (mdHACM) has reduced short term post-traumatic osteoarthritis (PTOA) progression in rats when delivered 24 hours after medial meniscus transection (MMT) and is being investigated for clinical use as a disease modifying therapy. Much remains to be assessed, including its potential for longer-term therapeutic benefit and treatment effects after onset of joint degeneration. Objectives: Characterize longer-term effects of acute treatment with mdHACM and determine whether treatment administered to joints with established PTOA could slow or reverse degeneration. Hypotheses: Acute treatment effects will be sustained for six weeks, and delivery of mdHACM after onset of joint degeneration will attenuate structural osteoarthritic changes. Methods: Rats underwent MMT or sham surgery (left leg). mdHACM was delivered intraarticularly 24 hours or 3 weeks post-surgery (n=5-7 per group). Six weeks post-surgery, animals were euthanized and left tibiae scanned using equilibrium partitioning of an ionic contrast agent microcomputed tomography (EPIC-µCT) to structurally quantify joint degeneration. Histology was performed to examine tibial plateau cartilage. Results: Quantitative 3D µCT showed that cartilage structural metrics (thickness, X-ray attenuation, surface roughness, exposed bone area) for delayed mdHACM treatment limbs were significantly improved over saline treatment and not significantly different from shams. Subchondral bone mineral density and thickness for the delayed treatment group were significantly improved over acute treated, and subchondral bone thickness was not significantly different from sham. Marginal osteophyte degenerative changes were decreased with delayed mdHACM treatment compared to saline. Acute treatment (24 hours post-surgery) did not reduce longer-term joint tissue degeneration compared to saline. Histology supported µCT findings and further revealed that while delayed treatment reduced cartilage damage, chondrocytes displayed qualitatively different morphologies and density compared to sham. Conclusions: This study provides insight into effects of intra-articular delivery timing relative to PTOA progression and the duration of therapeutic benefit of mdHACM. Results suggest that mdHACM injection into already osteoarthritic joints can improve joint health, but a single, acute mdHACM injection post-injury does not prevent long term osteoarthritis associated with meniscal instability. Further work is needed to fully characterize the durability of therapeutic benefit in stable osteoarthritic joints and the effects of repeated injections.